Tasawuf as a Pedagogical Foundation: Implementing Spiritual Values in Junior High School Education - Farhan, Ahmad (Journal of Sufism and Psychotherapy, 2025)
This study aims to examine the implementation of education and learning at the junior high school (SMP) level based on Sufi (tasawuf) values as a pedagogical foundation. The research method employed is library research with a critical analysis of Islamic education and Sufism literature. The findings reveal three key points: first, there is an essential alignment between Sufi values—such as sincerity (ikhlas), patience (sabr), and spiritual awareness (muraqabah)—and the goals of character education at the junior high school level. Second, Sufism offers an alternative pedagogical framework grounded in spirituality, integrating the spiritual dimension into the learning process, thus transforming it into a holistic journey of inner development. Third, modern Islamic education literature has not yet optimally integrated tasawuf as a pedagogical approach, indicating the need for curriculum reconstruction and the development of literature that incorporates Sufi principles. This study suggests that teachers, curriculum developers, and academics should more actively adopt Sufi-based values in formal education to shape students who are not only intellectually capable but also spiritually and morally mature. In doing so, junior high school education can significantly contribute to building a generation grounded in both knowledge and spiritual wisdom.